Optical filters based on microfiber knot resonator structure / Somayeh Nodehi - Somayeh, Nodehi (2016)
Microfiber Resonators are considered as an alternative waveguide due to their low-cost and accessible fabrication technology. This dissertation investigates combination of microfiber resonators for filter application. Also in this work thermal effect on complex structure is used to tune and modify filter factors. In the first section of this research this approach is applied to tune the extinction ratio of a microfiber Mach-Zhender-knot structure output. The same approach is used in a double-knot resonator to correct its optical path and increase the finesse. Then, a period pass-band filter based microfiber structure is proposed. The structure is made of successive microfiber knot resonators. As a result a periodical spectral filtering is obtained. In addition, an experimental investigation of the thermal effect on the spectral modulation of the structure is demonstrated. Several novel simple types of microfiber knot structures are introduced. These structures generate a periodic output spectrum with an adjustable band-pass using Vernier effect. The structures are combination of knot resonators with semi ring. It is calculated that the obtained finesse from the structure is bigger than that of a single knot. The structures with different size are fabricated in order to obtain various spectra with different bandwidth and increase the suppression ratio that resulted from Vernier effect. Finally, a single knot is used to investigate the nonlinearity (Kerr effect). The results are used to design an XOR gate. A comparison between thresholds power of stimulation this nonlinearity at passive and active microfiber are shown.